Gambogic Acid Lysinate-induced Cervical Cancer SiHa Cells Apoptosis in vitro and in vivo - Niu, Jie; Sun, Jingyu; Liu, Yahua; Guo, Jun; Zhang, Xin; Lin, Yajun (Anti-Cancer Agents in Medicinal Chemistry, 2023)
Background: Surgical resection and chemotherapy are the primary treatment options for cervical cancer; however, efficacy of chemotherapy drugs is limited by drug resistance. There is an urgent need to find new compounds. Gambogic acid lysinate (GAL), a new compound made from gambogic acid and lysine, has good anti-tumor activity, however, the effect of GAL on cervical cancer remains undetermined. Objective: The present study sought to explore the anti-tumor activity of GAL in SiHa cells. Methods: Cell viability was detected by means of an MTT assay, a cell growth curve was drawn with Microsoft Excel 2010, the cell cycle and cell apoptosis were evaluated by flow cytometry, and Western blotting was employed to explore the mechanism of GAL. Additionally, the in vivo anti-tumor activity of GAL was studied through a xenograft tumor model in nude mice. Results: GAL inhibited the proliferation of both SiHa cells (IC50 was 0.83 μmol/l and 0.77 μmol/l respectively for 48 h and 72 h) and HeLa cells (IC50 did not reach). In SiHa cells, GAL (1 and 2 μmol/l) inhibited cell proliferation and 2 μmol/l GAL could also induce cell apoptosis and decrease the number of S phase. Both 1 and 2 μmol/l GAL inhibited SiHa cells invasion and increased the number of G0/G1 phase. The results of Western blot assay demonstrated that P53 and P21 were involved in SiHa cells S phase arrest and BCL-2 and BAX were involved in SiHa cells apoptosis. In vivo study showed that the growth of SiHa cell xenograft tumors was inhibited via cell apoptosis induced by GAL (2.5 mg/kg body weight), however, GAL (2.5 mg/kg body weight) had no significant effect on weight gain of mice. Conclusion: GAL induced SiHa cells apoptosis by BCL-2 and BAX pathway and SiHa cells S phase arrest by P53 and P21 pathway in vitro and inhibited the growth of SiHa cell xenograft tumors.
Keywords: cervical cancer